Screening and Functional Analysis of TPO Gene Mutations in a Cohort of Chinese Patients With Congenital Hypothyroidism - Wang, Huijjuan; Wang, Wenxia; Chen, Xi; Shi, Hailong; Shi, Yinmin; Ding, Guifeng (Frontiers in Endocrinology, 2021)
Backgrounds: As a crucial enzyme in thyroid hormone synthesis, the genetic defective thyroid peroxidase (TPO) was one of the main genetic factors leading to congenital hypothyroidism (CH). Methods: Mutations in the TPO gene were screened and identified in 219 patients with CH from northwest China by using high-throughput sequencing and bioinformatics analysis. The biological function of detected variants was studied by in vitro experiments and homology modeling. Results: Nineteen rare variants, including seven novel ones, were detected in 17 of 219 patients (7.8%). Most cases were detected with one single heterozygous variant, and only two patients were detected with multiple variants, i.e., compounds for (1) IVS7-1G>A, p.Ala443Val, and p.Arg769Trp and (2) p.Asn592Ser and p.Asn798Lys. The biological function of the four missense mutations (i.e., p.Ala443Val, p.Arg769Trp, p.Asn592Ser, and p.Asn798Lys) they carried were further studied. Experimental data showed that these four mutations did not affect the protein expression level of the TPO gene but remarkably reduced the peroxidase activity toward guaiacol oxidation, retaining 8%–32% of activity of the wild-type protein. The comparison of the predicted 3-D structures of wild-type and mutant TPO proteins showed that these four amino acid substitutions changed the noncovalent interactions of studied residues that might alter the structure and function of the TPO protein. Conclusion: This study was the first to analyze the TPO mutation spectrum of patients with CH in northwest China. Our data indicated that the TPO mutation was not a common reason to cause CH in China. The functional data may help to clarify the structure- function relationship of the TPO protein and provide further evidence for the elucidation of the genetic etiology of CH.